The Management of New Student Admissions for SMA Muhammadiyah 2 Sidoarjo in the Covid-19 Pandemic Era: Manajemen Penerimaan Peserta Didik Baru SMA Muhammadiyah 2 Sidoarjo di Era Pandemi Covid-19 - Falaakhy, Muhammad Mauludy; Biyanto, Biyanto; Fahyuni, Eni Fariyatul (Universitas Muhammadiyah Sidoarjo, 2021)
At the end of May 2020, Nadiem Anwar Makarim, the Minister of Education issued a circular letter Number 4 of 2020, regarding the implementation of education policies during the Coronavirus Disease (Covid-19) emergency. In its application, many PPDB management activities must be able to adapt to the rules of the Indonesian government, therefore school management makes steps & policies related to PPDB related to planning, implementation, control so that they can get success. PPDB activities are an implementation process that is indispensable as process stability in the education sector. The Management function in its stages includes Planning, organizing, implementing, and supervising. The idea of management was put forward by Joseph Juran. There is a need for good quality planning and is known as Strategic Quality Management, namely the quality improvement process. Juran's concept is called the Juran Trilogy (1989) which states that quality management consists of three main parts, namely: (a) quality planning, (b) quality control, and (c) quality improvement. The purpose of this study was to obtain an overview of the management of new student admissions at the high school level during the Covid-19 pandemic. This research is a type of qualitative descriptive research model, with data collection techniques namely observation, interviews, documentation, and data triangulation. Based on the results of research conducted in SMA Muhammadiyah 2 Sidoarjo (SMAMDA), the researchers got the results of research that the implementation of acceptance of new students at SMAMDA went through several stages of selection that must be followed by prospective SMAMDA students, namely: Computer Based Test, Determination of Academic Values, Interviews and Urine test for all registration lines. Furthermore, the UPT PPDB will announce the results of the exam on the PPDB website for SMAMDA.